Factors Associated with the Four-Visit ANC in Indonesia: A population-based study - Helen Andriani; Valencia Natasha; Salma Dhiya Rachmadani; Adila Saptari (ACHSM, 2022)
Introduction: The number of maternal, neonatal and child mortality remains high in developing countries, including Indonesia. Antenatal care (ANC) coverage is an indicator of health-care use and access during pregnancy. Receiving at least four visits of ANC increases the chances of receiving appropriate maternal health interventions as one of the tracer indicators for universal health coverage in the Global Strategy for Women's, Children's, and Adolescents' Health Monitoring Framework (SDG indicator 3.8.1). The study aims to investigate the distribution and the factors associated with the four-visit ANC across urban and rural areas in Indonesia. Methods: We used data from the 2017 Indonesia Demographic and Health Survey, a large-scale nationally representative cross-sectional survey of women aged 15-49 years old (n=15,288). The use of ANC for the MNCH system is the dependent variable. The determinants are individual characteristics, family factors, and community factors. Results: Age, parity, household income, and distance from health facilities are significant factors associated with the four-visit ANC, as the first step in achieving continuum of care for MNCH. Urban women who had been pregnant 1-2 times or 3-4 times were 6.475 (95% Confidence Interval (95%CI) = 4.750-9.306) and 3.109 (95% CI = 2.268-4.262) times more likely to have at least four ANC visits than those who had been pregnant five times or more. Conclusion: Developing a health system, human resources, health facilities, and infrastructure are crucial for overcoming maternal and child health problems, especially in rural areas to make ANC universally affordable and accessible.